Evaluation of nitrogen fixation in the marine purple photosynthetic bacterium Rhodovulum sulfidophilum under autotrophic and heterotrophic conditions - Miki Suzuki; Tomokazu Shirai; Shamitha Rao Morey-Yagi; Akihiko Kondo; Keiji Numata (Scientific Reports)
Abstract Purple nonsulfur photosynthetic bacteria have metabolic pathways for the fixation of both carbon and nitrogen and show great potential as sustainable hosts for the production of materials such as amino acids, carotenoids, and bioplastics. They are predominantly mixotrophs capable of utilizing both organic and inorganic carbon sources for growth. However, most past studies on purple photosynthetic bacteria have focused on nitrogen fixation pathways independent of the extent of carbon fixation. In this study, we analyzed the nitrogen fixation ability of Rhodovulum sulfidophilum, a purple nonsulfur photosynthetic bacterium commonly found in estuaries where organic carbon and sulfur compounds are relatively abundant, by monitoring the uptake and conversion of 15N-labeled N2 gas to amino acids under autotrophic or heterotrophic conditions. Greater growth and 15N uptake were observed in the heterotrophic carbon metabolic state. Regardless of the type of amino acid, the efficiency of 15N uptake was greater under heterotrophic conditions, with a difference of approximately 2.1–2.6-fold observed on the third day of culture. This also corresponded to the growth rates under the different conditions. Therefore, our current findings confirm the nitrogen fixation ability of R. sulfidophilum under both heterotrophic and autotrophic conditions, with the heterotrophic mode favoring greater nitrogen fixation and assimilation.